β-Cyfluthrin biodegradation gene(s) associated in plasmid of Pseudomonas stutzeri (strain S1) - SINGH, JITENDRA; SINGH, DILEEP K; SANDHU, KIRAN VEER; JHA, SUNIL KUMAR; GOPAL, MADHUBAN (The Indian Journal of Agricultural Sciences, 2012)
Pseudomonas stutzeri strain S1 was found capable for biodegradation of β-cyfluthrin. Results indicated that the b- cyfluthrin degrading gene(s) of P. stutzeri strain S1 were located on a plasmid. This plasmid already had the gene(s) for nalidixic acid resistance. Another gene, Tn5 was inserted into the plasmid from Escherichia coli S17. The mutated P. stutzeri acquired resistance for nalidixic acid and kanamycin antibiotics and became incapable to degrade β-cyfluthrin. Probably insertion of Tn5 distressed the sequence of β-cyfluthrin degrading gene. This mutant was assayed to locate the β-cyfluthrin biodegrading gene. The mutant was able to transfer the Tn5 inserted plasmid in another strain of E. coli DH5a, which was confirmed by acquiring kanamycin resistance in E. coli (DH5a) and PCR analysis. Plasmid of the P. stutzeri S1 was eliminated using ethidium bromide along with heat shock treatment, and then this strain lost biodegradation activity of β-cyfluthrin. Thus, it has been validated that the biodegradation gene(s) were present on the plasmid. The plasmid was identified as a DNA circular molecule of 18.0 kb size.